Looking to London : stories of war, escape and asylum - Cockburn, Cynthia (Pluto Press, 2017)
"London is celebrated as one of the most ethnically diverse capitals in the world, and has been a magnet of migration since its origin. Looking to London steps into the maelstrom of current and recent wars and the resulting migration crisis, telling the stories of women refugees who have made it to London to seek safe haven amoung its many communities, under the watchful eye of the security services."